What Drives Migrants to Settle in Chinese Cities: a Panel Data Analysis - Gu, Hengyu; Jie, Yangyang; Li, Zhitao; Shen, Tiyan (Applied spatial analysis and policy, 2021)
Understanding the drivers of the floating population’s settlement intentions in Chinese cities is vital to guide evidence-based urban economic development policies. Prior studies have been inclined to use static cross-sectional analysis providing insights into the relative importance of the factors that drive the distribution of urban settlement intentions. Yet, little has adopted longitudinal data approaches to delve into their spatial-temporal patterns and changes in determinants. This study applies China Migrants Dynamic Survey data of 2014–2017 to examine the spatial distribution of urban settlement intentions of floating migrants and their determinants over time. It reveals a persistent and spatially differentiated pattern of urban settlement intentions, where floating migrants relocating to some small and medium-sized cities in several northern parts of China are more willing to settle down. Results from a two-way fixed-effects panel model indicate that both internal motivations and external constraints are closely related to the settlement decision process of floating migrants. The number of family members living together, marriage rate, duration of stay, insurance coverage, the average wage of employees, the proportion of employees in the education industry, and per capita fiscal expenditure positively correlate with settlement intentions, while the proportion of interprovincial floating migrants and urban employment rate have a negative relationship with settlement intentions. Our results further suggest that internal drivers are a prerequisite for external drivers to play a role in driving the urban settlement of migrants.